2001
DOI: 10.1148/radiol.2203010011
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Evaluation with Transvaginal US and Hysterosonography in Asymptomatic Postmenopausal Women with Breast Cancer Receiving Tamoxifen

Abstract: In asymptomatic postmenopausal women receiving tamoxifen, 6 mm is the optimal endometrial thickness cutoff for diagnosing endometrial abnormalities with transvaginal US. Further examination with hysterosonography can improve specificity by reducing the high false-positive rate of transvaginal US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…In asymptomatic women, the upper limit for normal endometrial thickness and the usefulness of TVS screening remain controversial. Various authors [8][9][10][11] have reported transvaginal sonographic endometrial thicknesses of 5, 9, and 10 mm as abnormal cut-off values for the identification of endometrial disease in asymptomatic perimenopausal women. However, the results of these studies 9,11 are limited by verification bias and by small sample size.…”
Section: Normal Appearance Of Endometrium On Tvsmentioning
confidence: 99%
See 2 more Smart Citations
“…In asymptomatic women, the upper limit for normal endometrial thickness and the usefulness of TVS screening remain controversial. Various authors [8][9][10][11] have reported transvaginal sonographic endometrial thicknesses of 5, 9, and 10 mm as abnormal cut-off values for the identification of endometrial disease in asymptomatic perimenopausal women. However, the results of these studies 9,11 are limited by verification bias and by small sample size.…”
Section: Normal Appearance Of Endometrium On Tvsmentioning
confidence: 99%
“…Various authors [8][9][10][11] have reported transvaginal sonographic endometrial thicknesses of 5, 9, and 10 mm as abnormal cut-off values for the identification of endometrial disease in asymptomatic perimenopausal women. However, the results of these studies 9,11 are limited by verification bias and by small sample size. [9][10][11] Recent study studying women on tamoxifen suggested that the optimal endometrial thickness cut-off for identification of abnormalities (polyps and submucosal fibroids) was > 6 mm, if maximal test accuracy (sensitivity and specificity) is desired.…”
Section: Normal Appearance Of Endometrium On Tvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonohysterography may be a useful adjunct for evaluating the patient with abnormal or dysfunctional uterine bleeding or to further clarify an abnormally thickened endometrium. 7 If the patient has an intrauterine contraceptive device, its location should be documented. (See the AIUM Practice Guideline for the Performance of Sonohysterography.…”
Section: B Uterusmentioning
confidence: 99%
“…Option B is not the best response. What constitutes the normal endometrial thickness for this group of patients is conSonography and Sonohysterography of Vaginal Bleeding troversial, with 5-8 mm having been proposed [5][6][7]. Option E is not the best response.…”
Section: Solution To Questionmentioning
confidence: 99%